2017
DOI: 10.7309/jmtm.6.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Validity of a GPS Monitor and a Smartphone Application to Measure Physical Activity

Abstract: Background: A recent approach to increasing physical activity levels, managing weight and improving health has been via technological advances, such as the Web 2.0 technologies, wearable activity trackers and smartphones. These approaches might be effective due to reduced cost, userfriendly environment and real-time feedback provided. Many of these monitors and smartphone applications are marketed to provide personal information on the level of physical activity, however little or no information is available r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…With ever-evolving smartphone applications and the increase in GPS tracking technology being used in sport, an analysis of a smartphone application and comparison with a range of GPS tracker devices currently used in sport was warranted. The use of smartphone technology to measure physical activity is nothing new as there has been objective studies that support the use of in this way and reported that these were reliable and valid [40,41]. The major findings of this study support studies that reported that a smartphone application can reliably monitor physical activity [42,35].…”
Section: Discussionsupporting
confidence: 76%
“…With ever-evolving smartphone applications and the increase in GPS tracking technology being used in sport, an analysis of a smartphone application and comparison with a range of GPS tracker devices currently used in sport was warranted. The use of smartphone technology to measure physical activity is nothing new as there has been objective studies that support the use of in this way and reported that these were reliable and valid [40,41]. The major findings of this study support studies that reported that a smartphone application can reliably monitor physical activity [42,35].…”
Section: Discussionsupporting
confidence: 76%
“…Overall, 11 different apps were tested, in which [ 15 , 19 , 28 , 32 , 37 , 42 ] studies were conducted using the My Jump and My Jump App 2, [ 17 , 18 , 27 , 30 , 34 , 38 , 44 , 46 ] the Powerlift, previously named Mylift, [ 36 ] the Ergo Arm Meter, [ 35 ] the Smartphone accelerometer, [ 33 , 41 ] the Speedclock App, [ 31 ] the MySprint App, [ 29 , 45 ] the ILoad, and [ 26 ] the Styrd App.…”
Section: Resultsmentioning
confidence: 99%
“…For the My Jump App and My Jump App 2, the ICC values of reliability were from 0.492–0.999 and CV values were between 3.4% and 12% [ 15 , 19 , 32 , 37 , 42 ]. For the PowerLift and My Lift App, the ICC values of reliability were 0.70–0.989 [ 17 , 18 , 27 , 30 , 44 , 45 ] and CV values were between 3.97% and 10.4% [ 17 , 27 , 30 , 34 , 44 ]. For the Ergo Arm Meter, the SEM value of reliability was <13.1º/s [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a very few information available about the validity of the data logged by the smartphone applications or wearable trackers since the sensors of the mobile devices are rarely tested for accuracy related to the physical activity records. Some studies, like [6], are showing reliable measures for distance while the energy expenditure estimation was low or even not very accurate at all compared with results coming from the medical devices. Technology can help to integrate physical activity into the health care standard by recommending the proper exercises to individuals based on the health records.…”
Section: Fig 2 Examples Of Wearable Devicesmentioning
confidence: 99%